PERSEPSI REMAJA MENGENAI RISIKO MASALAH KESEHATAN REPRODUKSI REMAJA (KRR) TERHADAP PEMANFAATAN PELAYANAN KRR OLEH SISWA SMA DI KECAMATAN PALU TIMUR KOTA PALU - , Triyani Widyaningsih ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: International Conference on Population and Development (ICPD) encourages governments and nongovernmental organizations (NGOs) to respond to the problems of adolescent sexual and reproductive health. Adolescents with numbers reaching 42.2 million (projected in 2002) or about 20% of the populations receive a lot of obstacles or problems that typically arise in the form of risky behavior on their health. Adolescent health problems include growth and development (physical and psychosocial changes), nutrition, drug abuse, and reproductive health including sexually transmitted infection / reproductive tract infections and HIV / AIDS. Adolescent reproductive health services should be provided in a friendly environment and their confidentiality should be highly maintained so that they can access the needed services. Objective: To assess perceptions of adolescents about the risks of adolescent reproductive health issues on adolescent reproductive health service utilization in health centers. Methods: This was an observational research with a cross-sectional design. This research was supported by qualitative data. The research was carried out in senior high schools within the working area of health centers in Palu. The samples were the first, second, and third graders consisting of 8 high schools, totaling 300 respondents. The research variables included the independent variable ie the perception of adolescents regarding the risks of ARH problem, the dependent variable ie ARH service utilization in health centers, and the extraneous variables ie knowledge and attitudes. The collection of data used questionnaires and in-depth interviews. The data were analyzed using univariable analysis, bivariable analysis with chisquare at p <0.05 and CI 95%, and multivariable analysis with logistic regression. Results: Analysis of utilization and perception demonstrated the value of RP = 1.5, CI95% = 1.02 to 2.24. The variables of utilization and perceptions remained to have a significant association after being controlled by the variable of attitude with RP = 1.5, CI95% = 1.07 to 2.36, meaning that students who had positive perceptions and attitudes about the risk of ARH problems would be likely to utilize ARH service more frequently by 1.5 times compared to students who had negative perceptions and attitudes about the risks of ARH problem. Conclusion: Adolescents who had positive perceptions and attitudes about the risk of ARH problems would be likely to utilize ARH services